Cerebroprotective prevention of memory disorders using sodium valproate - Ivanov, A. V. (Zaporozhye Medical Journal, 2013)
Epilepsy is the disease resulting in impaired cognitive function. The paper deals with the use of nootropics against the background of an anticonvulsant effect. Results of experiments on rats showed that investigated nootropics piracetam (500 mg/kg), citicoline (500 mg/kg), memantine (10 mg/kg) in combination with sodium valproate (80 mg/kg) improve memory and do not change its anticonvulsant effect.